2013
DOI: 10.1039/c3cp43877e
|View full text |Cite
|
Sign up to set email alerts
|

Anisole hydrolysis in high temperature water

Abstract: We investigated the hydrolysis of anisole to phenol in high-temperature water with and without water-tolerant Lewis acid catalysis. With no catalyst present, anisole hydrolyzes to phenol in 97% yield after 24 hours at 365 °C, our experimentally determined optimal temperature and time. Experiments with varied water density and analysis of comparable literature data suggest that anisole hydrolysis is almost third order in water, when the S(N)2 mechanism dominates. Of the water-tolerant Lewis acid catalysts studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…For example, cleavage of C-F bond in CF 3 -group is extremely demanding 16 . The same applies to C-O bond in the CH 3 O-group 17,18 .…”
mentioning
confidence: 97%
“…For example, cleavage of C-F bond in CF 3 -group is extremely demanding 16 . The same applies to C-O bond in the CH 3 O-group 17,18 .…”
mentioning
confidence: 97%
“…Research on model compounds has demonstrated that water-tolerant Lewis acids (i.e., metal triflates) facilitate the cleavage of C−O bonds in hydrolysis of guaiacol, benzyl phenyl ether, diphenyl ether, and anisole in a hydrothermal media. 31,32 It is considered that the Lewis acid (Al(OTf) 3 ) used in this study was capable of catalyzing the cleavage of C−O and some C−C bonds in glucose and cellulose in hydrothermal media. Solid yields from the runs with Al(OTf) 3 were low in comparison to the noncatalytic run and the catalytic runs with NaOTf.…”
Section: Resultsmentioning
confidence: 99%
“…If that value applies to the ether linkages in lignin, then these bonds are much more stable to hydrolysis than the bonds linking the subunits of cellulose and other biological polymers in water at pH 7 in the absence of an enzyme, as indicated in Table . Truly “uncatalyzed” ether hydrolysis has in fact been observed by several investigators, but only at temperatures (300–400 °C) approaching the critical point of water (374 °C). Assembling results from the literature for the hydrolysis of anisole in water, Rebacz and Savage have constructed an an Arrhenius plot that yields a Δ H ⧧ of 38 kcal/mol and an extrapolated rate constant of ∼10 –23 s –1 M –1 at 25 °C. That rate constant is several orders of magnitude slower than the rate constant estimated above for the H + -catalyzed reaction at pH 7, so that truly uncatalyzed hydrolysis is not expected to make a significant contribution to the rate of reaction in neutral solution except at temperatures above 300 °C.…”
Section: Resultsmentioning
confidence: 99%